MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN DENGAN MEDIA GAMBAR FOTOGRAFI BAGI ANAK KESULITAN BELAJAR ( Single Subject Research ) - Ririn Ryantika (Jurnal Penelitian Pendidikan Khusus, 2016)
Ririn Ryantika. 2016. "Improving Writing Ability Beginning With Media Image Photography for Children Learning Difficulties class II SDN 30 Lubuk Lintah" Thesis. Department of Special Education, Faculty of Education, University of Padang.Writing is one of the main factors in learning activities .Students who are not able to write well will have difficulty in participating in learning activities for all subjects, students will have difficulty in understanding the available information presented in various textbooks, books supporting materials and other learning resources written. This study discusses the improvement of writing skills beginning with the photographic image media for children learning difficulties.Starting from the observation that the researchers found when a child observation learning difficulties have not been able through the beginning stages of writing is writing the word correctly, until the observation after the treatment given to the target behavior kemampua write starters. The purpose of this study prove the photographic image media can improve children's ability to write the beginning of the learning difficulties. This research uses experimental approach in the form of single subject research (SSR) with multiple baseline design cross variables and data analysis using the technique of visual analysis chart.The data analysis showed that the first baseline before the intervention is given for 7 days with a mean level of 0.57 and a tendency toward increased slightly intervention was continued for 11 days with a mean level of 6.27, a tendency toward increased and improved data changes (+). Furthermore, a second baseline condition after the intervention carried out for 8 days with a tendency toward increased (+). The target behavior has a data overlape 0%. It was concluded that the photographic image media can improve children's writing skills beginning for learning difficulties. Based on the results of this study should teachers use a good media to practice writing skills beginning for children learning difficultiesKata Kunci :Kemampuan MenulisPermulaan; GambarFotografi; Anak KesulitanBelajar